2013
DOI: 10.1016/j.apgeochem.2013.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Processes affecting groundwater quality in arid zones: The case of the Bou-Areg coastal aquifer (North Morocco)

Abstract: The coastal aquifer of Bou-Areg (Morocco) has been studied to identify the main processes causing groundwater salinization, using a multi tracer (general chemistry and isotopes - delta H-2, delta O-18, delta C-13, delta N-15(NO3), delta O-18(NO3)) geochemical approach. Groundwater is characterized by the widespread occurrence of brackish waters (TDS < 500 mg L-1) with high cation contents, which are balanced by elevated dissolved NO3- (reaching a maximum of 208 mg L-1) and Cl-. Lagoon samples represent a mixtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 51 publications
4
29
0
Order By: Relevance
“…A preliminary investigation in the coastal aquifer of Bou-Areg and the adjacent lagoon of Nador was conducted to characterize aquifer recharge and salinization processes (Re et al, 2013a). Results showed that recharge is mainly due to mountain runoff, interacting with local recharge sources (ephemeral rivers and irrigation waters) resulting in a complex system of mixed waters.…”
Section: Introductionmentioning
confidence: 99%
“…A preliminary investigation in the coastal aquifer of Bou-Areg and the adjacent lagoon of Nador was conducted to characterize aquifer recharge and salinization processes (Re et al, 2013a). Results showed that recharge is mainly due to mountain runoff, interacting with local recharge sources (ephemeral rivers and irrigation waters) resulting in a complex system of mixed waters.…”
Section: Introductionmentioning
confidence: 99%
“…One data set depicts the salinity in the recent water and implies the anthropogenic factors as the most probable reasons for it, while the second data set consists of modern groundwater with higher salinity, which can be attributed to the dissolution of salts on infiltration through the saline soils (Re et al, 1996;Rao et al, 2014) Afterwards, the third data set appears to support the case of the surface salt dissolution, its leaching to the subsurface, and progressively increasing the groundwater salinity with time. It is clearly evident from the plot that the theory of dissolution and leaching can best stand as the mechanism for the salinity increase up to 4000 s/cm.…”
Section: The Salt Leaching Scenariomentioning
confidence: 95%
“…12 The Na/Cl ratio versus EC Fig. 13 The correlation between Cl − +SO 4 2 − and Na + +K + the water salinity origin and form a mixture tracer (Tellam 1995;Fidelibus and Tulipano 1996;Rajesh et al 2012;Ako et al 2012;Re et al 2013;Xing et al 2013). …”
Section: Relationship Between Chemical Elements and Groundwater Minermentioning
confidence: 99%
“…Among these studies, we cited the following: Benkabbour et al (2004), Zouhri et al (2008), Zouhri (2010), El Yaouti et al (2009, Re et al (2013), and Vinson et al (2013).…”
Section: Introductionmentioning
confidence: 98%